Formal framework for defining trust in multi-organisation environment. (2016) - Toumi, Khalifa; Andrés, César; Cavalli, Ana
Multi-organisations environment (MOE) is composed of several players that depend on each other for resources and services. Having a good access control policy to these resources becomes necessary. Moreover, being able to define a dynamic policy, meaning that it adapts over time, provides us with a more versatile way when administering these systems. In this paper, we extend the classical framework: organisation-based access control (OrBAC), adapted to MOE, adding trust information. Initially we present the theoretical framework to represent trust among organisations and users of the system, and then we present its inclusion in OrBAC as a new logical context for rule firing.